IMPROVEMENT THE SPATIAL RESOLUTION OF MULTICHANNEL AEROSPACE HIGH SPATIAL RESOLUTION IMAGES ON THE BASE OF HYPERSPHERICAL TRANSFORM - Hnatushenko, V. V.; Kavats, O. O.; Shevchenko, V. Yu. (Radio Electronics, Computer Science, Control, 2014)
In this paper we solve an actual problem of development of information technology to improve the visual quality of multi-channel space images of high spatial resolution. The object of the research is the process of fusing panchromatic and multispectral photogrammetric images obtained coordinate-sensitive sensors in the visible and infrared regions of the electromagnetic radiation. The subject of research are methods make preliminary and synergistic multi-channel data processing to improve the quality of the resulting image and reduce the color distortion. The purpose of the work is to increase the spatial resolution of the automated primary multi-channel images and compared with existing methods of eliminating color distortion in the local areas. In addition, the proposed technology will effectively carry out further recognition and real-time monitoring infrastructure. In the paper we propose a new information pansharpening technology based on HSV-converting and hyperspherical color conversion, which allows not only to improve the spatial resolution of the primary digital image, but also avoid the spectral distortion. This is achieved, in particular, by image pre-equalization, data processing localized spectral bases, optimized performance information, and the information contained in the infrared image. The software implementing proposed method is developed. The experiments to study the properties of the proposed algorithm are conducted. Experimental evaluation performed on eight-channel images obtained WorldView-2 satellite. Test results confirmed that the proposed approach can achieve high spectral and spatial quality multichannel images and outperforms existing methods.